Molecular Characterization of Echinococcus vogeli from Human Case, Colombia, 2024 - Jorge Alfredo Morcillo Muñoz; Diego Andrés Rodríguez-Lugo; Javier Hernández Moreno; María Helena Astorquiza; Luz Helena Patiño; Tatiana Marcela Cáceres; Angie Lorena Ramírez; Juan David Ramírez; Álvaro A. Faccini-Martínez (Emerging Infectious Diseases)
In Colombia, 35 confirmed cases of neotropical polycystic echinococcosis were reported during 1978–2018. In most cases, Echinococcus vogeli was identified by means of morphologic identification. We describe a case of E. vogeli echinococcosis in a woman, diagnosed through PCR, mitochondrial DNA sequencing, and molecular characterization.